The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ra04451h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of organic pollutants in wastewater via a Fenton-like process under the catalysis of HNO3-modified coal fly ash

Abstract: Organic wastewater can be treated effectively via a heterogeneous Fenton-like process under the catalysis of HNO3-modified coal fly ash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…On the other hand, when the H 2 O 2 dosage was deficient (0.5 mM), the removal of NAP also showed a dramatic decrease due to the oxidizing agent ( • OH) concentration in the reaction not being enough. These results are in good agreement with the results obtained by Wang et al [41]. Figure 6c,d shows the combined effect between temperature and pH on the removal efficiency of NAP.…”
Section: Effect Of Temperaturesupporting
confidence: 92%
“…On the other hand, when the H 2 O 2 dosage was deficient (0.5 mM), the removal of NAP also showed a dramatic decrease due to the oxidizing agent ( • OH) concentration in the reaction not being enough. These results are in good agreement with the results obtained by Wang et al [41]. Figure 6c,d shows the combined effect between temperature and pH on the removal efficiency of NAP.…”
Section: Effect Of Temperaturesupporting
confidence: 92%
“…Figure 4 (a) displays that Acid treatment is a comparatively better option for the enhancement of catalytic activity or activation of catalyst (coal fly ash). Wang et al recommended that the 12 h of impregnation is necessary for the good catalyst [66]. Material like activated carbon can be used as a modifier.…”
Section: Wet Impregnation Methodsmentioning
confidence: 99%
“…It can be judged by taking modifier or activator. Wang et al demonstrated that acid modified catalyst is more efficient than alkali [66]. They investigated that during the acid wash, alkaline catalyst gets neutralized by acid and also observed the increased surface area and pore volume, i.e.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, neutral pH can be used to reduce effluent costs. Also, Wang et al [68] had used HNO3-modified coal fly ash (HFA) to perform an oxidation reaction in the treatment of p-Nitrophenol pollutants, in which it is proven to be effective, stable, and reusable up to 9 runs of application with retaining removal percentage of > 91% after 9 runs. Increasing the temperature of the system does increase the efficacy of the treatment, but it is also imperative that the cost of said higher temperature be taken into account.…”
Section: Fenton-likementioning
confidence: 99%